Aqua training promotes changes of skeletal muscle mass in show jumping horses - C. Nascimento; C. Santos; M. Walton; T. Gonçalves; G. Freire; M. Nicolau; F. Silvestre; J. Simões; J. Borges; N. Pires; H. Manso Filho; H. Clayton; et al. (Journal of Equine Veterinary Science, 2026)

Nature's blueprint: Exopolysaccharides linking microbiome dynamics to advanced bone tissue engineering - Ceera Manikandan; Anupama Devi V.K.; Geetha Manivasagam; Ana Pereira; João F. Mano; João Borges; Amit Kumar Jaiswal; Anjaneyulu Udduttula (Carbohydrate Polymers, 2026)

Cross-cultural training and cultural intelligence of football coaches - Mário Borges; António Rosado; Francisco Freitas; Rita F. de Oliveira (German Journal of Exercise and Sport Research, 2026)
In today’s sports global market, coaches interact frequently with people from different cultures. This requires them to develop their awareness of cultural similarities and differences and their cultural intelligence (CQ) interacting across multiple cultures. This study assesses the effectiveness of an online lecture-based CQ training program for football coaches by examining the immediate knowledge retention and changes in attitude following participation. Data were collected through a Likert-scale questionnaire measuring coaches’ self-reported CQ before and after the training. The results showed no statistically significant differences between pre- and post-training scores, either in overall CQ or in its dimensions (metacognitive, motivational, behavioral, and cognitive CQ). This suggests that the training did not produce measurable changes in coaches’ CQ immediately after completion. Despite this, coaches scored the training as valuable and relevant to their professional practice. Limitations in the design and implementation of the training, such as its short duration and lack of cultural customization, may have limited its overall effectiveness. These findings can inform the design and implementation of more targeted cross-cultural training programs for sports professionals.

Habitat Suitability for a Unique, Fully Marine American Manatee ( Trichechus manatus ) Population Primarily Depends on Presence of Submarine Freshwater Springs - A. C. O. Meirelles; I. C. Normande; M. D. O. Alves; K. F. Choi; V. L. Carvalho; J. C. G. Borges; L. von Fersen; Andrew W. Trites (Marine Mammal Science, 2026)
The American manatee ( Trichechus manatus ) requires freshwater mainly from rivers and springs to maintain osmoregulatory balance in saline environments. However, in Brazil's semi‐arid Potiguar Basin, manatees now rely solely on submarine freshwater springs because hypersaline estuaries have become unsuitable sources of freshwater. We applied MaxEnt modeling to presence‐only data (sightings and filtered telemetry records) to produce habitat suitability maps and identify the environmental conditions driving habitat use. Telemetry locations were spatially and temporally thinned and subsampled to balance individual contributions, and alternative thinning scenarios were evaluated—while the model with the lowest level of spatial filtering showing the most stable performance was retained for inference. Model performance and fit were high (AUC = 0.979; CBI = 0.943, training gain = 2.76), and model suitability was strongly structured by proximity to submarine springs, with predicted probability declining sharply beyond 4–8 km. Seagrass presence contributed secondarily to suitability, whereas the other variables showed limited independent explanatory power at the regional scale. Suitable habitat was highly localized, comprising approximately 4% (301 km 2 ) of the modeled coastal area and concentrated near Icapuí (Ceará) and Areia Branca (Rio Grande do Norte). These findings reveal the strong ecological constraints shaping this fully marine manatee population and highlight the critical role of submarine freshwater springs and seagrass meadows in sustaining manatee presence in hypersaline coastal systems. Protecting these key resources is essential for conservation planning in a region facing increasing freshwater limitation and expanding offshore development.

Divergent metabolic strategies in two Aphanothece species (Cyanobacteria): Interactive effects of temperature and light intensity on growth, pigment composition, and lipid profile - Ronald Tarazona Delgado; Rui dos Santos Ferreira Filho; Mariana F. G. Assunção; Berk Aksoy; Lília M. A. Santos; Carlos Rafael Borges Mendes (Journal of Applied Phycology, 2026)
Temperature and light intensity are among the most influential environmental factors modulating cyanobacterial physiology, yet their interactive effects on metabolite accumulation remain understudied in several genera with biotechnological potential. In this study, the influence of temperature (12, 20 and 28 °C) and light intensity (60, 120 and 180 µmol photons m −2 s −1 ) on the growth, pigment profile, and lipid composition of two Aphanothece strains ( A. microscopica and A. stagnina ) was evaluated through a 3 2 full factorial design. Both species exhibited strain-specific responses across all measured parameters. In A. microscopica , high temperature and low light promoted the accumulation of chlorophyll a , phycobiliproteins (particularly phycocyanin and allophycocyanin), and a diversified carotenoid profile including echinenone and myxoxanthophyll. In contrast, A. stagnina showed higher pigment productivity under high temperature combined with high irradiance, particularly enriching zeaxanthin and β-carotene. Lipid content increased in both strains under low temperature and moderate light, suggesting a compensatory metabolic route under suboptimal growth conditions. Fatty acid analysis revealed major differences: A. microscopica displayed a complex profile dominated by palmitic acid and enriched with polyunsaturated fatty acids under cold treatments, while A. stagnina exhibited reduced diversity, with monounsaturated fatty acids, especially palmitoleic and myristic acids, prevailing under all conditions. These findings underscore the metabolic flexibility of Aphanothece species in response to environmental variation and highlight their differentiated potential for applications in biorefineries. Selective cultivation of each strain under tailored conditions may enhance the yield of specific pigments or lipids, supporting their use in biofuel, nutraceutical, and cosmeceutical industries. Graphical Abstract

Influence of Conspecific Male Odour and Host Kairomones on the Behaviour of Sternochetus mangiferae, a Pest of Mangoes in Brazil and Ghana - Miguel Borges; Mirian F. F. Michereff; Raúl A. Laumann; József Vuts; Marla J. Hassemer; João Victor C Machado; Michely F. S. Aquino; Kamila K S Leite; Alessandra de Carvalho Silva; Marcelo P Ricalde; Haruna Braimah; Michael A. Birkett; et al. (Journal of Chemical Ecology, 2026)
Sternochetus mangiferae is a pest of mangoes, occurring worldwide in regions where mangoes are cultivated. In Brazil, this insect was first detected in 2014 in Seropédica, Rio de Janeiro, and since then, various measures and studies have been conducted to contain, monitor and potentially eradicate it. Semiochemicals may provide feasible targets to develop sensitive detection and monitoring tools. Therefore, this study aimed to evaluate whether S. mangiferae use pheromones from conspecifics and kairomones from mango tree host in their chemical communication. The findings identify a blend of mango volatiles that influence the behaviour of S. mangiferae females. A synthetic blend containing the EAD-active compounds γ-butyrolactone, benzaldehyde, 6-methyl-5-hepten-2-one, myrcene, ( Z )-ocimene, 2-methoxyphenol, ( S )-linalool, methyl salicylate and methyl benzoate was attractive to females of S. mangiferae from Ghanaian and Brazilian populations in two-choice olfactometry experiments. The results also indicate that the absolute configuration of linalool in the mango synthetic blend is crucial for female attraction, as females respond only to blends containing ( S )-linalool. Furthermore, females from both populations were attracted to the odour of live males from their respective localities. Chemical analysis of aeration samples from the Brazilian population revealed that males and females emitted qualitatively similar volatile profiles. Although no male-specific compounds could be identified to fully explain female attraction, this study provides the first evidence of intraspecific chemical communication in S. mangiferae . These findings advance our understanding of the chemical ecology of this pest and support the development of semiochemical-based monitoring and management strategies for mango orchards.

Taxonomic and functional diversity of urban bees of the world - João C. F. Cardoso; Pietro K. Maruyama; Ingrid N. Gomes; Lorena B. Valadão‐Mendes; Victor H. D. Silva; Larissa Lorraine; Jordana O. Borges; Rogério V. Gonçalves; Léo C. Rocha‐Filho; Renata Trevizan; Yasmine Antonini (Conservation Biology, 2026)
Bees play a pivotal role in terrestrial environments. Urbanization can affect these organisms and the ecosystem services they provide. However, knowledge of the global diversity of urban bees is limited. Thus, we summarized data on urban bee species identities and occurrences; compared distributions of all bees with those found in urban environments; described traits and resource collection across latitudinal regions; and determined species’ conservation status. We identified 1981 urban bee species, representing 9.5% of overall diversity. Nontropical regions had more studies and higher bee richness than tropical regions, indicating geographical bias. Family distributions of urban bees were similar to those observed for overall bee diversity. The Apidae family accounted for 35.1% of urban species worldwide. In the tropics, Apidae accounted for 69.0%. Most urban bees of the world were solitary (49.8%) and social (33.8%) (eusocial, 4.7%; kleptoparasite, 11%), were medium (41.8%) to small sized (36.2%), nested in soil rather than cavities (65.0%), and had the capacity to perform buzz pollination (65.0%). Only a small proportion of bees collected specialized resources (oil, 3.2%; resin, 12.1%; fragrance, 2.9%) and plant material (10.7%). Due to the dominance of Apidae, this situation differed in the tropics, where there was a higher degree of social (42.9%) and eusocial habits (20.1%), more large‐sized species (42.9%), more cavity‐nesting species (62.7%), and especially a higher representation of specialized resource collection, including oil (10.7%), resin (44.2%), and fragrance (17.6%). Most species (96.4%) had not had their conservation status evaluated. Our results showed that urban environments worldwide can support a high taxonomic and functional diversity of bees, but that this capacity differed across latitudes. Our findings can be used to inform management strategies that promote suitable nesting sites and provide specific resources for bees in each global region, making cities more bee friendly and maintaining the ecosystem services bees provide.

Observations on the natural history of the ant-garden, Azteca paraensis bondari Borgmeier, 1937 (Formicidae, Dolichoderinae) - Rebeca Q. Menezes; Jacques H. C. Delabie; Cléa S. F. Mariano; Elmo Borges de Azevedo Koch (International Journal of Tropical Insect Science, 2026)

Differential presence of microplastics in the gastrointestinal tract of tropical fish in relation to trophic levels - Merle M. Borges-Ramírez; Rosa E. Martínez-Cerda; Carlos E. Paz-Ríos; Edgar F. Mendoza-Franco; Atahualpa Sosa-López; Jaime Rendón-von Osten (Regional Studies in Marine Science, 2026)

Mermaids in pools: Ex-situ conservation as a cornerstone for sirenian management worldwide - D.N. Castelblanco-Martínez; E.A. Ramos; A. Alvarez-Aleman; L. von Fersen; R.S. Amaral; F.L.N. Attademo; J.C.G. Borges; L.J. Cabrias-Contreras; D. Caicedo-Herrera; T. Calleson; V.L. Carvalho; A. Dávila-Peñaloza; et al. (Journal for Nature Conservation, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Beyond the Highlands: Climate Drives Evolutionary Connections Between Ancient Neotropical Mountains and Lowland Biomes - Yago Barros‐Souza; Monique Maianne; Rafael F. Barduzzi; Leonardo M. Borges (Global Ecology and Biogeography, 2026)
Aim The assembly of montane plant communities through time is underlain by historical and abiotic factors. However, the extent of evolutionary connectivity between ancient highland ecosystems and surrounding lowlands remains unclear. Here, we investigate the evolutionary connections between the campos rupestres , a hyperdiverse and fragmented montane vegetation complex in eastern South America, and lowland biomes surrounding it: savannas, rainforests and seasonally dry tropical forests. Location Eastern South America. Time Period Cenozoic. Major Taxa Studied Flowering plants. Methods Using phylogenetic beta diversity analyses for 13 angiosperm clades, we assess the degree of lineage dissimilarity between campos rupestres subregions and adjacent biomes. We also apply generalised dissimilarity modelling to determine the role of climate, soil and geographic distance in shaping spatial patterns of phylogenetic composition. Results Our results reveal high lineage permeability between campos rupestres and surrounding biomes, with lineage sharing largely reflecting biome adjacency. This pattern is mainly driven by shared climatic conditions, which are the strongest predictors of phylogenetic dissimilarity. Main Conclusions We highlight the importance of lineage exchange between lowland and montane environments for the assembly of highland floras. By showing that lineage movements across biome boundaries have been common over time and across spatial scales, our study challenges the idea that ancient Neotropical mountains are isolated sky‐islands. Instead, we emphasise the dynamic nature of montane plant diversity and the pivotal role of climate in shaping evolutionary connections between highlands and lowlands.

Characterization of AHL-mediated quorum sensing in Pseudomonas gessardii from raw milk and insights into control of proteolytic activity - Mohammed Kamal Salman; Irene Giordano; Giuseppina Tommonaro; Adele Cutignano; Sérgio F. Sousa; Anabela Borges; Gianluigi Mauriello; Gennaro Roberto Abbamondi (International Journal of Food Microbiology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Do Island Spiders Descend From Trees? – A Tale of Island Colonisation and Niche Expansion - R. Costa; N. Macías‐Hernández; F. Rigal; P. A. V. Borges; P. Cardoso (Journal of Biogeography, 2025)
Aim Oceanic islands are known for being home to drastically different communities compared to the mainland, as their isolation and limited area significantly favour clades able to travel long distances over water. On spiders, this happens mainly, although not exclusively, through ballooning whose propensity is unevenly distributed across species and requires specific conditions, possibly influencing their microhabitat distribution. However, once reaching the islands, colonisers might shift their preferences towards microhabitats with less competition. In this study, using Macaronesian spiders as models, we aim to test whether: (1) the closest mainland relatives to island endemics occupy higher vertical strata; (2) island endemics show niche shift and expansion towards lower vertical strata (lower vertical distribution and larger range compared to their closest mainland relatives); (3) active hunters show a larger vertical niche shift and expansion than web‐weavers. Location Macaronesia (Azores, Madeira and Canary Islands). Taxon Spiders (Arachnida: Araneae). Methods We selected the closest relatives from a comprehensive phylogenetic tree encompassing Iberian and Macaronesian forest spiders. We tested our hypotheses using null models and paired Wilcox non‐parametric tests followed by linear models. Results The mainland lineages did show higher average verticality than expected by chance. However, despite showing a significantly larger vertical range, and contrary to our expectations, island endemics display higher average verticality than their mainland lineages. Furthermore, hunters showed an increase in mean verticality, while web‐weavers tended to be those decreasing, with both guilds showing no differences in the variation of vertical range separately. Main Conclusions Spiders living in higher layers in mainland forests have a higher probability of reaching oceanic islands; yet, not all show a preference to grab opportunities at ground level. Although this is possibly due to the presence of ground‐dwelling competitors/predators or the past extinction of epigean species, the transition observed further supports the colonisation filter favouring more arboreal species.

Carbon-related processes as indicators of soil health in a degraded dryland area under long-term restoration: Responses of a 21-year grazing exclusion system - Antonio Y.V. Lima; Maurício R. Cherubin; Danilo F. Silva; Ademir S.F. Araujo; Diogo P. Costa; Jaedson C.A. Mota; Ícaro V. Nascimento; Alexandre S. Queiroz; Erika V. Medeiros; Kaio G.V. Garcia; Gabriel N. Nóbrega; Geocleber G. Sousa; et al. (Applied Soil Ecology, 2025)

Geostatistical uncertainty maps for real-world efficient AUV data collection - Ana F. Duarte; Lucrezia Bernacchi; Renato Mendes; João Borges de Sousa; Leonardo Azevedo (Frontiers in Marine Science, 2025)
Autonomous Underwater Vehicle (AUV) trajectory planning for oceanographic surveys is challenging and requires comprehensive and efficient data collection for enhanced mission success. By strategically navigating and targeting high-value data points, the AUV can operate longer and gather more essential information for numerical ocean model calibration. Here, we propose a geostatistical modelling workflow with two complementary objectives. First, to jointly predict ocean temperature and spatial uncertainty maps, representing regions with limited knowledge about the ocean properties of interest, from where optimized navigation paths can be devised and updated. Second, to efficiently assimilate the collected data and update an ocean model with the new data. An autonomous oceanographic survey performed off W. Portugal illustrates the proposed modelling workflow. We use the CMEMS product of Atlantic-Iberian-Biscay-Irish-Ocean Physics Analysis and Forecast as a priori and conditioning data of the spatial predictions. During the survey, the data acquired by the AUV are assimilated and used in new geostatistical predictions for the day after the data acquisition. The results show that the proposed methodology efficiently predicts daily ocean temperature and its spatial uncertainty, allowing data assimilation from different sources (i.e., numerical models of ocean dynamics and AUV sampling). This approach enables the assimilation of AUV measurements and the model prediction to have higher value and greater reliability.

Influence of Inorganic Nutrients on a North Atlantic Microbial Community’s Response to Ocean Alkalinity Enhancement - Inês de Castro; Susana C. Ribeiro; António Louvado; Newton Carlos Marcial Gomes; Mário Cachão; Paulo F. Silva Borges; Eduardo Brito de Azevedo; Joana Barcelos e Ramos (Oceans, 2025)
Ocean Alkalinity Enhancement (OAE) is a promising carbon dioxide removal strategy, but its ecological impacts on marine microbial communities under varying nutrient conditions remain poorly understood. We conducted laboratory incubations using a natural North Atlantic microbial assemblage to investigate the response to OAE under both natural and nutrient-enriched regimes. We tracked phytoplankton and bacterioplankton dynamics, biomass, and leucine aminopeptidase (LAP) and alkaline phosphatase (ALP) activity as indicators of organic matter remineralization. OAE consistently reduced phytoplankton abundance in both nutrient regimes, potentially due to CO2 limitation, resulting in lower production of phytoplankton-derived organic matter. This reduction was reflected in decreased LAP activity and shifts in the relative abundance of phytoplankton-associated bacterial taxa. These findings indicate that OAE can directly affect phytoplankton through carbonate chemistry alterations, with potential microbial responses largely mediated by changes in organic matter availability. While short-term microbial disruptions were modest, the ecological consequences of altered bloom dynamics should be carefully considered in future OAE deployment strategies.

Exploring the therapeutic synergy: comprehensive assays unveil the potential of sericin and Chelidonium majus L. in developing a possible wound dressing - Ana Borges; Sandrina A. Heleno; Sónia P. Miguel; Maximiano P. Ribeiro; Paula Coutinho; André F. Moreira; María Luisa Martín Calvo; Josiana A. Vaz; Lillian Barros; Ricardo C. Calhelha (Phytochemistry Letters, 2025)

Enhancing wound healing: sericin and Chelidonium majus L. as potential dressings - Ana Borges; María Luisa Martín Calvo; Sandrina A. Heleno; Sónia P. Miguel; Maximiano P. Ribeiro; Paula Coutinho; André F. Moreira; Josiana A. Vaz; Lillian Barros; Ricardo C. Calhelha (Phytochemistry Letters, 2025)

Season and temperature-humidity index affect sperm quality and in vivo fertility of beef bulls - Larysse A. Alves; Reinaldo F. Cooke; Marcelo Sant’Ana Borges; Fabiana F. Souza; John P. Kastelic; André M. Crespilho (Journal of Thermal Biology, 2025)

Gene-Specific Substitution Rates for the Vespertilionidae (Chiroptera: Mammalia) Mitochondrial Genome, with the Description of Three new Mitogenomes - M. S. Borges; M. M. A. Salles; E. F. Oliveira; F. M. Magalhães; D. C. Silva; H. F. M. Oliveira; K. C. Faria; V. N. Laine; T. M. Lilley; J. M. Silva; F. M. C. B. Domingos (Journal of Molecular Evolution, 2025)

P31-27 Mitochondria-Targeted Edaravone Derivatives as Neuroprotective Agents - S. Barreiro; F. Cagide; F. Borges; F. Remião; R. Silva (Toxicology Letters, 2025)

P31-01 Exploring a novel 3-Hydroxypyridin-4-one Derivative as a Disease-Modifying Drug Candidate for Parkinson's Disease - V. Silva; S. Benfeito; I. Costa; C. Lima; D. Chavarria; D. Barbosa; F. Remião; F. Borges; R. Silva (Toxicology Letters, 2025)

Spatiotemporal analysis of the bovine brucellosis vaccination rate in Minas Gerais, Brazil, from 2011 to 2022 - Anna Cecilia Trolesi Reis Borges Costa; Yasmim Domingos da Silva; Julio Silvio de Souza Bueno Filho; James F. Lowe; Andrey Pereira Lage; Luciana Faria de Oliveira; Elaine Maria Seles Dorneles (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Removing pollutants and recovering resources in treatment wetlands cultivated with ora-pro-nobis and citronella - L. S. Lopes; T. S. Alves; A. M. Araújo; F. F. Cunha; A. P. Rosa; A. C. Borges (International Journal of Environmental Science and Technology, 2025)

Measuring the natural capital of Amazonian forests: A case study of the National Forest of Carajás, Brazil - Tereza Cristina Giannini; Caroline Oliveira Andrino; Rafael Gomes Barbosa-Silva; José A. Bitencourt; Rafael C. Borges; Renata R. Brito; Rosane Cavalcante; Claudia P.W. Costa; Sidnei Dantas; Markus Gastauer; Vitor F. Gomes; Ulysses M. Maia; et al. (Ecosystem Services, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Enhanced apoptosis, inflammatory cellularity, collagen deposition, and interaction between fibroblasts and Leishmania amastigotes in undamaged ear skin of dogs with leishmaniosis - Barbara Laurice Araújo Verçosa; Maria Imaculada Muniz-Junqueira; Luciano de F. Borges; Maria Norma Melo; Anilton Cesar Vasconcelos (Veterinary Parasitology, 2025)

Advances in Legume Systematics 15: Integrating knowledge on the legume family - Leonardo M. Borges; Marcelo F. Simon; Tânia M. Moura; Luciano P. Queiroz; Marianne Le Roux (Brazilian Journal of Botany, 2025)

Zinc and Cadmium Remediation in Contaminated Soil by CaCO3-Biochar Material from Sugar Beet Industry - Roger Borges; Matheus B. Soares; Mariana P. Pollo; Luís Reynaldo F. Alleoni; Amanda S. Giroto; Maraisa Gonçalves; Michael Müller; Nicolai D. Jablonowski; Caue Ribeiro (Water, Air, & Soil Pollution, 2025)

Multi-Step Forecasting of Meteorological Time Series Using CNN-LSTM with Decomposition Methods - Eluã Ramos Coutinho; Jonni G. F. Madeira; Dérick G. F. Borges; Marcus V. Springer; Elizabeth M. de Oliveira; Alvaro L. G. A. Coutinho (Water Resources Management, 2025)

In silico studies and in vitro evaluation of isatin-pyridine oxime hybrids as novel reactivators of acetylcholinesterase inhibited by an A-230 surrogate - Leandro B. Bernardo; Leandro A. Vieira; Caio V. N. Borges; Pedro A. G. Buitrago; Kamil Kuča; Tanos C. C. França; Samir F. A. Cavalcante; Roberto B. Sousa; Antônio L. S. Lima; Daniel A. S. Kitagawa (Archives of Toxicology, 2025)

Shared Pheromone Compounds in Neotropical Rice Stink Bugs: The Role of Zingiberenol and Sesquipiperitol - M. C. Blassioli-Moraes; A. Khrimian; M. F. F. Michereff; D. M. Magalhães; J. V. M. Costa; E. R. Hickel; J. A. Barrigossi; R. A. Laumann; S. D. Guggilapu; J. Grazia; M. Borges (Journal of Chemical Ecology, 2025)

Persistent organic pollutants and fatty acids in humpback whales: Antarctic and Chilean feeding and Brazilian breeding sites - Cristian T. Timoszczuk; Satie Taniguchi; Josilene da Silva; Lucas Costa Pereira; Luciano Dalla Rosa; Eduardo R. Secchi; Javier Negrete; João Carlos Gomes Borges; Salvatore Siciliano; Paula Baldassin; Jorge Acevedo; Anelio Aguayo-Lobo; et al. (Science of The Total Environment, 2025)

Pollen evolution in the Stryphnodendron clade (Leguminosae, Mimoseae) - Rafael F. Barduzzi; Yago Barros-Souza; Stefany Liau-Kang; Leonardo M. Borges (Brazilian Journal of Botany, 2024)

Colonisation by multidrug-resistant organisms in health workers in primary care: narrow spectrum oral antimicrobials are a risk factor - Vítor Falcão de Oliveira; Letícia Fernandes de Britto-Costa; Gabrielly Lacerda de Aragão; Nazareno Scaccia; Ana Carolina Mamana; Marina Farrel Côrtes; Maura Salaroli de Oliveira; Bruno de Melo Tavares; Erika Regina Manuli; Fábio Eudes Leal; Gabriela Tonon de Oliveira Xavier; Regina Maura Zetone Grespan; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - F. Javelle; W. Bloch; U. Borges; T. Burberg; B. Collins; N. Gunasekara; T. J. Hosang; T. Jacobsen; S. Laborde; A. Löw; A. Schenk; M. L. Schlagheck; et al. (European Journal of Applied Physiology, 2024)
Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

Chemical and visual stimuli for conservation biological control of stink bugs in soybean: potential use and flaws on egg parasitoid recruitment - Ana Carolina G. Lagôa; Pedro H. B. Togni; Michely F. Aquino; Maria Carolina Blassioli-Moraes; Miguel Borges; Raúl A. Laumann (BioControl, 2024)

Synthesis and in vitro assessment of the reactivation profile of clinically available oximes on the acetylcholinesterase model inhibited by A-230 nerve agent surrogate - Leandro B. Bernardo; Caio V. N. Borges; Pedro A. G. Buitrago; Kamil Kuča; Samir F. A. Cavalcante; Roberto B. Sousa; Antônio L. S. Lima; Daniel A. S. Kitagawa (Archives of Toxicology, 2024)

P04-08 Insights into the mechanistic pathways underlying the neurotoxic effects of 2C-I and 25I-NBOMe drugs - E. Gil-martins; F. Cagide; A. Borer; D.J. Barbosa; C. Fernandes; F. Remião; F. Borges; R. Silva (Toxicology Letters, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Upper Cretaceous Crustacea from Central Cuba - Francisco J. Vega; Torrey Nyborg; Alessandro Garassino; Giovanni Pasini; Javier Aguilar-Pérez; Carlos R. Borges-Sellén; Alberto F. Arano-Ruiz; Servilio J. Quintero-Vázquez; Roberto Manuel Gutiérrez-Domech (Journal of South American Earth Sciences, 2024)

Successful cryopreservation in biodegradable containers of sperm from aquaculture Mediterranean fishes - T.S. França; W.A. González-López; M.P. Sanchez; L. Ferrão; F. Fernández-García; L.P. Borges; A. Belenguer; P.G. Holhorea; J.C. Calduch-Giner; A. Felip; A. Gómez; J. Pérez-Sánchez; et al. (Theriogenology, 2024)

A spatiotemporal analysis of bovine brucellosis cases in Minas Gerais state, Brazil, from 2011 to 2018 - Anna Cecilia Trolesi Reis Borges Costa; Suman Bhowmick; James F. Lowe; Andrey Pereira Lage; Luciana Faria de Oliveira; Elaine Maria Seles Dorneles (Preventive Veterinary Medicine, 2024)

Structural-based analysis of sulfonamide derivatives: from solid states to acetolactate synthase enzyme interactions - Antônio S. N. Aguiar; Rogério F. Costa; Leonardo L. Borges; Lucas D. Dias; Hamilton B. Napolitano (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

David versus Goliath: Early career researchers in an unethical publishing system - Aurore Receveur; Jonathan Bonfanti; Stephanie D'Agata; Andrew J. Helmstetter; Nikki A. Moore; Brunno F. Oliveira; Cathleen Petit‐Cailleux; Erica Rievrs Borges; Marieke Schultz; Aaron N. Sexton; Devi Veytia (Ecology Letters, 2024)
The publish‐or‐perish culture in academia has catalysed the development of an unethical publishing system. This system is characterised by the proliferation of journals and publishers—unaffiliated with learned societies or universities—that maintain extremely large revenues and profit margins diverting funds away from the academic community. Early career researchers (ECRs) are particularly vulnerable to the consequences of this publishing system because of intersecting factors, including pressure to pursue high impact publications, rising publication costs and job insecurity. Moving towards a more ethical system requires that scientists advocate for structural change by making career choices that come with risks, many of which disproportionately impact ECRs. We illuminate major issues facing ECRs in Ecology and Evolution under the current publishing system, and propose a portfolio of actions to promote systemic change that can be implemented by ECRs and established researchers.

Food for healthier aging: power on your plate - Denise Mafra; Stephanie Ariemu Ugochukwu; Natalia A Borges; Ludmila F. M. F Cardozo; Peter Stenvinkel; Paul G. Shiels (Critical Reviews in Food Science and Nutrition, 2024)

Investigating an extreme meteo-oceanographic event in the southern Brazil from in situ observations and modeling results - Dayanis M. Borges; Humberto L. Varona; Marcelo F. Alonso; Moacyr Araujo; Fabrice Hernandez (Regional Studies in Marine Science, 2023)

Carbon dioxide and methane capture in metal-organic framework MIL-101(Cr) at high pressure - Tamires R. Menezes; Kátilla M.C. Santos; Thauane S.L. Silva; Klebson S. Santos; André L. Ramos; Gustavo R. Borges; Elton Franceschi; Cláudio Dariva; Juliana F. De Conto; Silvia M. Egues; Cesar C. Santana (Gas Science and Engineering, 2023)

Spatiotemporal variability of dissolved inorganic macronutrients along the northern Antarctic Peninsula (1996–2019) - Thiago Monteiro; Sian F. Henley; Ricardo César Gonçalves Pollery; Carlos Rafael Borges Mendes; Mauricio Mata; Virginia Maria Tavano; Carlos Alberto Eiras Garcia; Rodrigo Kerr (Limnology and Oceanography, 2023)
The northern Antarctic Peninsula is a key region of the Southern Ocean due to its complex ocean dynamics, distinct water mass sources, and the climate‐driven changes taking place in the region. Despite the importance of macronutrients in supporting strong biological carbon uptake and storage, little is known about their spatiotemporal variability along the northern Antarctic Peninsula. Hence, we explored for the first time a 24‐year time series (1996–2019) in this region to understand the processes involved in the spatial and interannual variability of macronutrients. We found high macronutrient concentrations, even in surface waters and during strong phytoplankton blooms. Minimum concentrations of dissolved inorganic nitrogen (DIN; 16 μ mol kg −1 ), phosphate (0.7 μ mol kg −1 ), and silicic acid (40 μ mol kg −1 ) in surface waters are higher than those recorded in surrounding regions. The main source of macronutrients is the intrusions of Circumpolar Deep Water and its modified variety, while local sources (organic matter remineralization, water mass mixing, and mesoscale structures) can enhance their spatiotemporal variability. However, we identified a depletion in silicic acid due to the influence of Dense Shelf Water from the Weddell Sea. Macronutrient concentrations show substantial interannual variability driven by the balance between the intrusions of modified Circumpolar Deep Water and advection of Dense Shelf Water, which is largely modulated by the Southern Annular Mode (SAM) and to some extent by El Niño‐Southern Oscillation (ENSO). These findings are critical to improving our understanding of the natural variability of this Southern Ocean ecosystem and how it is responding to climate changes.

P21-25: Targeting iron dysregulation and oxidative stress for the development of innovative therapeutics against neurodegeneration - R. Oliveira; A.R. Alfenim; P. Soares; F. Borges; F. Remião; C. Fernandes; R. Silva (Toxicology Letters, 2023)

Cultural intelligence in sport: An examination of football coaches’ cross-cultural training needs - Mário Borges; António Rosado; Babett Lobinger; Francisco Freitas; Rita F. de Oliveira (German Journal of Exercise and Sport Research, 2023)
Cultural intelligence is the capability of a person to adapt effectively to different cultures. This capability has been investigated in areas such as management, military, and education. However, there are no studies in sport referring to this capability. It is important to study cultural intelligence in sport because of the increased globalisation resulting from coaches’ and athletes’ migration across countries and clubs. This study aimed to develop the Cultural Intelligence in Sport (CQsport) and examine its factorial structure and psychometric properties; and examine coaches’ cultural intelligence and their perceived cross-cultural training needs. Participants were 209 football coaches either with or without international experience. Participants completed an online survey consisting of CQsport and a cross-cultural training needs questionnaire. We used a multigroup analysis, within the structural equation model (SEM) approach, to test group differences in the CQsport and performed a one-way analysis of variance (ANOVA) for comparisons across groups concerning cross-cultural training needs. Coaches with international experience rated themselves with more cultural intelligence in the sports context than coaches with no international experience on the metacognitive, cognitive, motivational and behavioural dimensions. Coaches with international experience also self-rated fewer training needs than coaches without international experience. This study represents the first attempt to examine football coaches’ cultural intelligence and their cross-cultural training needs.

Powdery mildew (Erysiphe cruciferarum) on Brassicaceae in Brazil - Rafaela C. F. Borges; Stéfani dos Santos Leite; João Marcos T. Martins; Maria D. M. Santos; Josiene S. Veloso; Nuno R. Madeira; Maria Esther N. Fonseca; Leonardo S. Boiteux; Ailton Reis (Australasian Plant Pathology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

A human modified Pseudokossmaticeras brandti (Ammonitina: Kossmaticeratidae) from the late Campanian of Cuba and the species distribution in the Caribbean province - Esteban López-Murillo; Carlos Rafael Borges-Sellén; Alberto F. Arano-Ruiz; Lázaro W. Viñola-López; Yasmani Ceballos-Izquierdo; Johanset Orihuela; Neil H. Landman (Journal of South American Earth Sciences, 2023)

3D structured photocatalysts for sustainable H2O2 generation from saccharides derivatives - Rita A. Borges; Marta F. Pedrosa; Yaidelin A. Manrique; Cláudia G. Silva; Adrián M.T. Silva; Joaquim L. Faria; Maria J. Sampaio (Chemical Engineering Journal, 2023)

Assessing water quality of Paraopeba River (Minas Gerais, Brazil) after the rupture of tailings dam - F. V. Fonseca; A. M. F. Linhares; J. R. P. Silva; L. L. S. Silva; I. D. Bassin; J. P. Bassin; F. A. Kronemberger; A. C. Habert; C. P. Borges (International Journal of Environmental Science and Technology, 2023)

Rhomb-I, a P–I metalloproteinase from Lachesis muta rhombeata venom degrades vessel extra cellular matrix components and impairs platelet aggregation - Valéria Gonçalves de Alvarenga; Luciana S. Oliveira; Gustavo O. Santos; Dan E. Vivas-Ruiz; Márcia Helena Borges; Rodrigo C.G. de Souza; Johannes A. Eble; Ana Maria Moura-da-Silva; Eladio F. Sanchez (Toxicon, 2023)

Dietary addition of recombinant Bacillus subtilis expressing a fungal phytase increases phosphorus fixation in muscle of Pacific white shrimp Litopenaeus vannamei - Luiza Medeiros; Bruna Nornberg; Raíza Azevedo; Arthur Cardoso; Victor Torres Rosas; Marcelo Borges Tesser; Virgínia F. Pedrosa; Luis A. Romano; Wilson Wasielesky; Luis Fernando Marins (Aquaculture International, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

The effects of resistance exercise on appetite sensations, appetite related hormones and energy intake in hormone receptor-positive breast cancer survivors - Sarah A. Purcell; Edward L. Melanson; Anosheh Afghahi; Virginia F. Borges; Isabella Sinelli; Marc-Andre Cornier (Appetite, 2023)

Curcumin and 10-undecenoic acid as natural quorum sensing inhibitors of LuxS/AI-2 of Bacillus subtilis and LasI/LasR of Pseudomonas aeruginosa - Susana Fernandes; Anabela Borges; Inês B. Gomes; Sérgio F. Sousa; Manuel Simões (Food Research International, 2023)

A technological approach using a metal-free immobilized photocatalyst for the removal of pharmaceutical substances from urban wastewaters - Maria J. Sampaio; Ana R.L. Ribeiro; Cláudia M.R. Ribeiro; Rita A. Borges; Marta F. Pedrosa; Adrián M.T. Silva; Cláudia G. Silva; Joaquim L. Faria (Chemical Engineering Journal, 2023)

Acute food deprivation-induced relapse to heroin seeking after short and long punishment-imposed abstinence in male rats - C. Borges; F. Inigo; N. Quteishat; J. Charles; E. Ah-Yen; Shalev U. (Psychopharmacology, 2023)

Fast Identification Method for Screening Bacteria from Faecal Samples Using Oxford Nanopore Technologies MinION Sequencing - Ana Sofia G. Borges; Meghna Basu; Erik Brinks; Corinna Bang; Gyu-Sung Cho; John F. Baines; Andre Franke; Charles M. A. P. Franz (Current Microbiology, 2023)
Most bacterial identification methods require extensive culturing, strain purification and DNA extraction protocols. This leads to additional expenses and time lags when isolating specific bacteria from complex microbiological ecosystems. This study aimed to develop a fast and robust method for identification of lactobacilli, bifidobacteria and Bacteroides in human faecal samples. Bacteria from faecal samples were cultured anaerobically on selective media. Sonication-based DNA extraction was performed, followed by almost complete 16S rRNA gene polymerase chain reaction amplification and MinION sequencing with the Flongle adapter. Sequence analysis was performed using NanoCLUST, while RStudio was used for graphics. For 110 of the 125 colonies investigated, 100% of reads were attributed to a single species, while the remaining 15 colonies consisted of mixtures of up to three different species. The proposed bacterial identification method is advantageous for isolating particular bacteria for which there are no exclusively selective media, as it avoids lengthy colony purification and DNA purification methods, and yields a quick colony identification with high accuracy. Therefore, this method can be used for directly screening for pure cultures of target microorganisms and is suitable for the identification of bacteria in culturomics studies.

Clinical and Parasitological Evaluation of Ivermectin and Ivermectin + Pyrantel Against Oxyuris Equi in Equines - Vinícius D. Rodrigues; Mariana G. de Freitas; Bruno Milan; Guilherme H. Reckziegel; Dyego G.L. Borges; Matheus T.M. Nakatani; Juliane F. Tutija; Fernando de A. Borges (Journal of Equine Veterinary Science, 2023)

Ultrastructural study of Manihot esculenta amyloplast: intragranular channels and membrane lipid profiling - Osman F. Silva; André L. A. Guimarães; Ricardo M. Borges; Cristina T. Andrade; Veronica Calado (Brazilian Journal of Botany, 2023)

Anti-inflammatory potential of baicalein combined with silk fibroin protein in a zebrafish model (Danio rerio) - Fabrício H. Holanda; Arlefe N. Ribeiro; Brenda L. Sánchez-Ortiz; Gisele C. de Souza; Swanny F. Borges; Adriana M. Ferreira; Alexandro C. Florentino; Sérgio A. Yoshioka; Lienne S. Moraes; José Carlos T. Carvalho; Irlon M. Ferreira (Biotechnology Letters, 2023)

Influence of pigeon pea (Cajanus cajan) on oviposition behaviour of Diceraeus melacanthus stink bug, an important pest of soybean and maize crops in South America - M. Borges; M. F. F. Michereff; R. A. Laumann; G. T. Santana; B. S. Castro; C. C. Silva; M. C. Blassioli-Moraes (Arthropod-Plant Interactions, 2023)

Mixed circuit training acutely reduces arterial stiffness in patients with chronic stroke: a crossover randomized controlled trial - André C. Michalski; Arthur S. Ferreira; Adrian W. Midgley; Victor A. B. Costa; Guilherme F. Fonseca; Nádia S. L. da Silva; Juliana Borges; Sandra A. Billinger; Felipe A. Cunha (European Journal of Applied Physiology, 2023)

Characterization of Colletotrichum isolates causing anthracnose on Artocarpus heterophyllus in Brazil - Rafaela C. F. Borges; Maurício Rossato; Maria D. Mendes Santos; Willie Anderson dos Santos Vieira; Marcos P. S. Câmara; Ailton Reis (Journal of Plant Pathology, 2022)

Hyperglycemia alters N-glycans on colon cancer cells through increased production of activated monosaccharides - H. F. Loponte; I. A. Oliveira; B. C. Rodrigues; R. Nunes-da-Fonseca; R. Mohana-Borges; F. Alisson-Silva; W. B. Dias; A. R. Todeschini (Glycoconjugate Journal, 2022)

In vitro and in silico cytotoxicity of hinokinin-loaded PLGA microparticle systems against tumoral SiHa cells - Regiane G. de Lima; Flavia C. R. Lisoni; Thais B. Picão; Fransérgio F. dos Santos; Renato P. Orenha; Alexandre Borges; Eduardo F. Molina; Renato L. T. Parreira; Márcio L. A. e Silva; Mario F. C. Santos; Rosangela da S. de Laurentiz (Natural Product Research, 2022)

Induced Stress and Tactile Stimulation Applied to Primiparous does and their Consequences on Maternal Behavior, Human-Animal Relationships, and Future Offspringˊs Sexual Disorders - Angela C. F. Oliveira; Luiza M. Bernardi; Ana Larissa B. Monteiro; Kassy G. Silva; Saulo H. Weber; Tâmara D. Borges; Antoni Dalmau; Leandro B. Costa (Veterinary Research Communications, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

Indoor-outdoor pollutant concentration modelling: a comprehensive urban air quality and exposure assessment - J. L. Santiago; E. Rivas; R. Buccolieri; A. Martilli; M. G. Vivanco; R. Borge; O. S. Carlo; F. Martín (Air Quality, Atmosphere & Health, 2022)
This paper is devoted to the investigation of the relationship between concentrations of traffic-related pollutants at pedestrian level in the street and indoor pollutant concentrations inside different rooms of different floors of a standard building. CFD modelling covering the whole urban environment, including the interior of a target building, is used to explicitly simulate wind flow and pollutant dispersion outdoors and indoors. A wide range of scenarios considering different percentage and location of open windows and different wind directions is investigated. A large variability of indoor pollutant concentrations is found depending on the floor and configuration of the open/closed windows, as well as the wind direction and its incidence angle. In general, indoor pollutant concentrations decrease with floor, but this decrease is different depending on the scenario and the room investigated. For some conditions, indoor concentrations higher than the spatially averaged values in the street (up to a ratio of 1.4) are found in some rooms due to the high pollutant concentrations close to open windows. This behavior may lead, on average, to higher exposure inside the room than outside although, in general, indoor pollutant concentrations are lower than that found in the street at pedestrian level. Results are averaged for all scenarios and rooms being the average ratio between indoor and oudoor concentrations 0.56 ± 0.24, which is in accordance with previous studies in real buildings. This paper opens to a unified approach for the assessment of air quality of the total indoor and outdoor environment.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Dietary supplementation of Synechococcus elongatus PCC 7942 expressing a heterologous β-glucosidase on the expression of genes related to digestion, immune system, and antioxidant defenses of the shrimp Litopenaeus vannamei - Luiza Medeiros; Raíza Azevedo; Jade Riet; Bruna Nornberg; Arthur Cardoso; Victor Torres Rosas; Marcelo Borges Tesser; Virgínia F. Pedrosa; Luis A. Romano; Wilson Wasielesky; Luis Fernando Marins (Journal of Applied Phycology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Asbestos cement waste treatment through mechanochemical process with KH2PO4 for its utilization in soil pH correction and nutrient delivery - Roger Borges; Amanda S. Giroto; Gelton G. F. Guimarães; Heitor P. G. Reis; Cristiane S. Farinas; Caue Ribeiro (Environmental Science and Pollution Research, 2022)

Connecting Amazonian historical biogeography and local assemblages of understorey birds: Recurrent guild proportionality within areas of endemism - Pilar L. M. Braga; Sérgio H. Borges; Carlos A. Peres; Bette A. Loiselle; John G. Blake; Juliana Menger; Anderson S. Bueno; Marina Anciães; Fernando H. Teófilo; Marina F. A. Maximiano; Affonso H. N. Souza; Roberta L. Boss; et al. (Journal of Biogeography, 2022)
Aim Current diversity patterns in local communities result from historical and contemporary events that operate at distinct spatial and temporal scales. However, the contribution of local and large‐scale processes in structuring species diversity remain a contentious topic in ecology. We investigated diversity patterns (species richness, composition and number of captures) of understorey bird assemblages in Amazonian unflooded ( terra firme ) forests. We sought to understand whether understorey bird assemblages in distinct areas of endemism show distinct patterns of diversity, and whether species replacements among areas of endemism occur while the proportion of species within guilds remains stable. Location Amazonia. Taxon Understorey birds. Methods To investigate diversity patterns, we compiled studies that mist‐netted birds at 11 regions across seven Amazonian areas of endemism. We used coverage‐based rarefaction curves, non‐metric multidimensional scaling (NMDS) and created a heatmap based on the proportion of captures in each area of endemism to access patterns of richness, composition and captures of understorey birds, respectively. The relative variance (RVgp index) was calculated to investigate the existence of guild proportionality within each area of endemism. Results Bird assemblages diverged across the seven areas of endemism, in terms of species richness, composition and captures. However, the proportion of species and individuals within guilds was similar among areas of endemism, indicating that species replacements across areas of endemism occur while maintaining the same ecological functions. Guild proportionality suggests that interspecific competition and resource availability are more important than environmental heterogeneity in structuring understorey bird assemblages. Main conclusions The similar proportion of species within guilds suggest that interspecific competition and resource availability are more important than environmental heterogeneity in structuring local assemblages, possibly via a process of limiting similarity in morphological and functional traits. The observed congruent structure in understorey bird assemblages across areas of endemism shows that coupled historical and ecological processes, operating at local to large scales, have led to current patterns of diversity and composition in Amazonian bird communities.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Combining Knowledge Systems Helps Understand the Spatial Dynamics of Data-Limited Small-Scale Fisheries Systems in Brazil: A Methods Analysis - Rebecca Borges; Indira A. L. Eyzaguirre; Roberta Sá Leitão Barboza; Karin Boos; Marion Glaser; Priscila F. M. Lopes (Frontiers in Marine Science, 2021)
Mangrove habitats provide nursery, shelter, and feeding sites for many economically relevant fish, and invertebrates, such as crabs. Given the highly artisanal character and the patchy spatial distribution of small-scale fishing in mangroves, there is often little data available to inform management, potentially threatening the sustainability of this livelihood-supporting activity. This study assesses the combination of different data collection methods and of including published data in the analysis of the spatial dynamics. We examine crab fisheries in two sustainable-use protected areas as a case study to understand use patterns as indicated by a specific combination of mapping methods. Mangrove crab fishing grounds were mapped by overlaying crab gatherers’ tracked routes with maps produced during participatory-mapping-centered interviews. Information from the literature was used to spatialize crab carapace width and relate it to distance traveled by fishers. Results show that crabs tended to be larger if caught farther from the villages where fishers live. In terms of collection methods, even though GPS tracking is relatively time- and resource-consuming, incorporating some GPS tracking into participatory mapping helps overcome a downside of this type of mapping (e.g., lack of geographical precision) and identifies information that can be accessed through participatory techniques. This highlights the importance of linking different approaches in order to understand small-scale fisheries spatial dynamics.

Counting Carbon: Quantifying Biomass in the McMurdo Dry Valleys through Orbital & Field Observations - Mark R. Salvatore; John E. Barrett; Schuyler R. Borges; Sarah N. Power; Lee F. Stanish; Eric R. Sokol; Michael N. Gooseff (International Journal of Remote Sensing, 2021)

Invasion and Extirpation Potential of Native and Invasive Spartina Species Under Climate Change - Francisco O. Borges; Catarina P. Santos; José R. Paula; Enrique Mateos-Naranjo; Susana Redondo-Gomez; Janine Barbara Adams; Isabel Caçador; Vanessa F. Fonseca; Patrick Reis-Santos; Bernardo Duarte; Rui Rosa (Frontiers in Marine Science, 2021)
Coastal areas host some of the planet’s most productive ecosystems, providing life-sustaining ecological services and several benefits to humankind, while also being some of the most threatened areas (e.g., by globalization, climate change, and biological invasion). Salt marshes are coastal habitats with a key role in food and shelter provisioning, sediment deposition, nutrient cycling and carbon storage. Spartina spp. is a genus of grass halophytes which occurs in salt marshes worldwide, and includes species with different invasive potential. We evaluated the effect of climate change in the distribution and invasion potential of five Spartina species ( S. anglica , S. alterniflora , S. densiflora , S. patens , and S. maritima ) at a global scale. Species distribution models (SDMs) were applied on species occurrence data and atmospheric environmental predictors (WorldClim 2.1) to project potential changes in habitat suitability and associated changes in distribution and species co-occurrence until the end of the century, across four Shared Socioeconomic Pathway scenarios (i.e., SSP1-2.6 to SSP5-8.5). Projections showed a global trend for increasing species co-occurrence, with a general range expansion potentiated by increasing pathway severity. This study suggests that Spartina species can potentially benefit from climate change, predicting poleward expansions in the Northern Hemisphere for most species, with results pointing at increased conflict and invasion potential in Northern Europe and East Asian shorelines, already under strong invasive pressure. S. anglica is projected to remain a successful invader, with more severe scenarios likely favoring greater expansions. S. alterniflora exhibits very low expansion comparatively, despite exhibiting the same northward distribution shift. SSP1-2.6 produced the smallest change to species co-occurrence, suggesting a smaller potential for invasion-related conflicts, although still registering a potential net expansion for the Genus. Despite their limitations, SDMs can help establish general trends in climate change ecology and inform policymakers and environmental agents to ensure the correct management of these habitats and, ultimately, ecosystems.

Priming of indirect defence responses in maize is shown to be genotype-specific - Mirian F. F. Michereff; Priscila Grynberg; Roberto C. Togawa; Marcos M. C. Costa; Raúl A. Laumann; Jing-Jiang Zhou; Pedro H. C. Schimmelpfeng; Miguel Borges; John A. Pickett; Michael A. Birkett; Maria Carolina Blassioli-Moraes (Arthropod-Plant Interactions, 2021)

Field Responses of Rice Stalk Stink Bug, Tibraca limbativentris, to Synthetic Sex Pheromone and Isomers of 1,10-Bisaboladien-3-ol - Thais F S De Freitas; E R Hickel; Ashot Khrimian; Miguel Borges; Mirian F F Michereff; José Alexandre Barrigossi; Raúl Alberto Laumann; S D Guggilapu; Josué Sant’Ana; Maria Carolina Blassioli-Moraes (Neotropical Entomology, 2021)

Colletotrichum siamense as a causal agent of leaf anthracnose in seedlings of Annona muricata in nurseries from the Federal District, Brazil - Rafaela C. F. Borges; Maurício Rossato; Maria D. Mendes Santos; Mônica A. Macedo; M. E. N. Fonseca; L. S. Boiteux; A. Reis (Journal of Plant Diseases and Protection, 2021)

Effect of the hydroxamate group in the antitumoral activity and toxicity toward normal cells of new copper(II) complexes - Nathália F. B. Azeredo; Franz V. Borges; Marcelo S. Mathias; Jackson A. L. C. Resende; Roberto W. A. Franco; Milton M. Kanashiro; Adolfo Horn; Christiane Fernandes (BioMetals, 2021)

Release-Recapture Test of Dispersal and Survival of Sterile Males of Ceratitis capitata (Diptera: Tephritidae) - F Duarte; M V Calvo; S Delgado; A Bartolucci; A Asfennato; A Borges; I Scatoni; F M García (Neotropical Entomology, 2020)

Hydrocarbon Contamination Patterns in the Cenotes of the Mexican Caribbean: The Application of Principal Component Analysis - J. A. León-Borges; F. Viveros-Jiménez; A. E. Rodríguez-Mata; M. A. Lizardi-Jiménez (Bulletin of Environmental Contamination and Toxicology, 2020)

A novel approach for subsurface characterization of coupled fluid flow and geomechanical deformation: the case of slightly compressible flows - M. R. Borges; F. Pereira (Computational Geosciences, 2020)

Human Losses and Damage Expected in Future Earthquakes on Faial Island–Azores - J. Fontiela; P. Rosset; M. Wyss; M. Bezzeghoud; J. Borges; F. Cota Rodrigues (Pure and Applied Geophysics, 2020)

Male-Produced Sex Pheromone of Tibraca limbativentris Revisited: Absolute Configurations of Zingiberenol Stereoisomers and their Influence on Chemotaxis Behavior of Conspecific Females - M. C. Blassioli-Moraes; A. Khrimian; M. F. F. Michereff; D. M. Magalhães; E. Hickel; T. F. S. de Freitas; J. A. F. Barrigossi; R. A. Laumann; A. T. Silva; S. D. Guggilapu; C. C. Silva; J. Sant’Ana; et al. (Journal of Chemical Ecology, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Effect of biotin supplementation on milk yield of Girolando cows reared in a tropical climate - P. J. B. Queiroz; D. C. Silva; P. A. C. Borges; A. C. B. R. Pedroso; A. P. A. Vinhal; R. E. Rabelo; L. A. F. Silva (Tropical Animal Health and Production, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Influence of constitutive and induced volatiles from mature green coffee berries on the foraging behaviour of female coffee berry borers, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae) - M. C. Blassioli-Moraes; M. F. F. Michereff; D. M. Magalhães; S. D. Morais; M. J. Hassemer; R. A. Laumann; A. M. Meneghin; M. A. Birkett; D. M. Withall; J. N. Medeiros; C. M. C. Corrêa; M. Borges (Arthropod-Plant Interactions, 2019)

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Crown gall caused by Agrobacterium tumefaciens species complex: a novel nursery disease of Tectona grandis in Brazil - Rafaela C. F. Borges; Maurício Rossato; Greecy Mirian R. Albuquerque; Maria A. Ferreira; Ana C. M. Brasileiro; Maria Esther N. Fonseca; Leonardo Silva Boiteux (Journal of Plant Pathology, 2019)

A leaf spot of Tectona grandis caused by Xanthomonas fuscans in Brazil - Rafaela C. F. Borges; Maurício Rossato; Maria do Desterro M. Santos; Cléia S. Cabral; Greecy Mirian R. Albuquerque; Maria A. Ferreira; Maria Esther N. Fonseca; Leonardo Silva Boiteux (Journal of Plant Pathology, 2019)

Variability in herbivore-induced defence signalling across different maize genotypes impacts significantly on natural enemy foraging behaviour - Mirian F. F. Michereff; Diego M. Magalhães; Marla J. Hassemer; Raúl A. Laumann; Jing-Jiang Zhou; Paulo E. de A. Ribeiro; Paulo A. Viana; Paulo E. de O. Guimarães; Pedro H. C. Schimmelpfeng; Miguel Borges; John A. Pickett; Michael A. Birkett; et al. (Journal of Pest Science, 2019)

Beyond the Last Glacial Maximum: Island endemism is best explained by long‐lasting archipelago configurations - Sietze J. Norder; Konstantinos Proios; Robert J. Whittaker; María R. Alonso; Paulo A. V. Borges; Michael K. Borregaard; Robert H. Cowie; F. B. Vincent Florens; António M. de Frias Martins; Miguel Ibáñez; W. Daniel Kissling; Lea de Nascimento; et al. (Global Ecology and Biogeography, 2019)
Aim To quantify the influence of past archipelago configuration on present‐day insular biodiversity patterns, and to compare the role of long‐lasting archipelago configurations over the Pleistocene to configurations of short duration such as at the Last Glacial Maximum (LGM) and the present‐day. Location 53 volcanic oceanic islands from 12 archipelagos worldwide—Azores, Canary Islands, Cook Islands, Galápagos, Gulf of Guinea, Hawaii, Madeira, Mascarenes, Pitcairn, Revillagigedo, Samoan Islands and Tristan da Cunha. Time period The last 800 kyr, representing the nine most recent glacial–interglacial cycles. Major taxa studied Land snails and angiosperms. Methods Species richness data for land snails and angiosperms were compiled from existing literature and species checklists. We reconstructed archipelago configurations at the following sea levels: the present‐day high interglacial sea level, the intermediate sea levels that are representative of the Pleistocene and the low sea levels of the LGM. We fitted two alternative linear mixed models for each archipelago configuration using the number of single‐island endemic, multiple‐island endemic and (non‐endemic) native species as a response. Model performance was assessed based on the goodness‐of‐fit of the full model, the variance explained by archipelago configuration and model parsimony. Results Single‐island endemic richness in both taxonomic groups was best explained by intermediate palaeo‐configuration (positively by area change, and negatively by palaeo‐connectedness), whereas non‐endemic native species richness was poorly explained by palaeo‐configuration. Single‐island endemic richness was better explained by intermediate archipelago configurations than by the archipelago configurations of the LGM or present‐day. Main conclusions Archipelago configurations at intermediate sea levels—which are representative of the Pleistocene—have left a stronger imprint on single‐island endemic richness patterns on volcanic oceanic islands than extreme archipelago configurations that persisted for only a few thousand years (such as the LGM). In understanding ecological and evolutionary dynamics of insular biota it is essential to consider longer‐lasting environmental conditions, rather than extreme situations alone.

Lactobacillus spp. impair the ability of Listeria monocytogenes FBUNT to adhere to and invade Caco-2 cells - P. Castellano; M. Pérez Ibarreche; L. Longo Borges; F. C. Niño Arias; G. R. Ross; E. C. Pereira De Martinis (Biotechnology Letters, 2018)

A global spatially explicit database of changes in island palaeo‐area and archipelago configuration during the late Quaternary - Sietze J. Norder; John B. Baumgartner; Paulo A. V. Borges; Tomislav Hengl; W. Daniel Kissling; E. Emiel van Loon; Kenneth F. Rijsdijk (Global Ecology and Biogeography, 2018)
Motivation Past sea level fluctuations have shaped island area and archipelago configuration. The availability of global high‐resolution data on bathymetry and past sea levels allows reconstruction of island palaeo‐geography. Studies on the role of palaeo‐area often consider only the Last Glacial Maximum, which neglects the dynamics of island fusion and fission resulting from cyclic sea level fluctuations throughout the Quaternary. Currently, no global database is available to test the role of changing island geographies driven by Quaternary sea level change on evolutionary, ecological and archaeological patterns. However, data on island palaeo‐environments is crucial for understanding insular biodiversity distributions and human settlement patterns. Here, we present the Palaeo‐Islands and Archipelago Configuration (PIAC) database, containing sea level‐driven palaeo‐geography changes over the late Quaternary of 178 islands in 27 archipelagos, and discuss its relevance, limitations and uncertainties. The R functions developed to create the PIAC database are provided to allow calculations for other islands, time steps, sea‐level curves and higher spatio‐temporal resolutions. Main types of variables contained Polygon shapefiles with archipelago configuration and tables with palaeo‐area per island. Spatial location and grain The database has a global representation, with 27 archipelagos being covered: Aldabra, Azores, Balearic Islands, California Channel Islands, Canary Islands, Cape Verde, Comoros, Cook Islands, Crozet Islands, Dutch Caribbean, Galápagos, Gulf of Guinea, Hawaii, Inner Seychelles, Juan Fernández, Kuril Islands, Madeira, Marianas, Marquesas, Mascarenes, Phoenix Islands, Pitcairn Islands, Prince Edward Islands, Revillagigedo, Samoan Islands, Society Islands and Tristan da Cunha. All data are at 1 km 2 spatial resolution. Time period and grain The focus of this paper is on the last 35 kyr; data for the last 140 kyr are also provided. The grain is 1 kyr temporal resolution. Level of measurement Data are per island, grouped per archipelago. Software format The data were produced in the R programming language.

Age Influence on Sexual Behavior of the Lesser Cornstalk Borer, Elasmopalpus lignosellus (Zeller) (Lepidoptera: Pyralidae) - L M S Xavier; D M Magalhães; P A Viana; M C Blassioli-Moraes; M Borges; J A F Barrigossi; E F Vilela; R A Laumann (Neotropical Entomology, 2018)

Pre-culture in endothelial growth medium enhances the angiogenic properties of adipose-derived stem/stromal cells - Lucas E. B. Souza; Liziane R. Beckenkamp; Lays M. Sobral; Daianne M. C. Fantacini; Fernanda U. F. Melo; Josiane S. Borges; Andréia M. Leopoldino; Simone Kashima; Dimas Tadeu Covas (Angiogenesis, 2018)

The Inclusion of Chitosan in Poly-ε-caprolactone Nanoparticles: Impact on the Delivery System Characteristics and on the Adsorbed Ovalbumin Secondary Structure - Sandra Jesus; Elizangela H. Fragal; Adley F. Rubira; Edvani C. Muniz; Artur J. M. Valente; Olga Borges (AAPS PharmSciTech, 2018)

Use of 3D printing for biofuel production: efficient catalyst for sustainable biodiesel production from wastes - M. E. Borges; L. Hernández; J. C. Ruiz-Morales; P. F. Martín-Zarza; J. L. G. Fierro; P. Esparza (Clean Technologies and Environmental Policy, 2017)

Factors Influencing Anaerobic Biodegradation of Biodiesel Industry Wastewater - Erlon L. Pereira; Alisson C. Borges; Fernanda F. Heleno; Tiago H. C. Costa; Ann H. Mounteer (Water, Air, & Soil Pollution, 2017)

Larval development and allometric growth of the black‐faced blenny Tripterygion delaisi - F. N. Solomon; D. Rodrigues; E. J. Gonçalves; E. A. Serrão; R. Borges (Journal of Fish Biology, 2017)
Larval development and allometric growth patterns of the black‐faced blenny Tripterygion delaisi are described from a larval series (body length, L B = 3·30–12·10 mm) caught by light traps at the Arrábida Marine Park, Portugal. Larvae of T. delaisi possess distinctive morphometric and meristic characteristics which can be used to identify this species from related taxa. Pigmentation is sparse but characteristic, consisting of pigmented eyes, gas bladder pigmentation in the dorsal region, anal pigmentation and a row of regularly spaced postanal ventral melanophores. This pattern is present from as early as the yolk‐sac stage and persists throughout all stages with just the addition of head and caudal pigmentation during the flexion and postflexion stages, respectively. The majority of fin development (with the exception of the caudal fin), occurs in the later stages of development. Myomere counts range between 37 and 45 for all stages. Growth is allometric during larval development. When inflexion points of growth were detected, growth was found to be biphasic with the inflexion points occurring within a very narrow range of L B (8·70–8·90 mm) close to the mean ± s.d. (9·44 ± 1·48 mm L B ) of postflexion larvae. Considering allometric growth patterns and ontogenetic descriptions together, the first developmental phase includes the preflexion and flexion stage larvae, while the second phase characterises the postflexion larvae prior to the transition from larvae to juvenile.

Genotypic and phenotypic detection of capsular polysaccharide and biofilm formation in Staphylococcus aureus isolated from bovine milk collected from Brazilian dairy farms - Alessandra P.S. Salimena; Carla C. Lange; Cecilia Camussone; Marcelo Signorini; Luis F. Calvinho; Maria A.V.P. Brito; Cristiano A.V. Borges; Alessandro S. Guimarães; João B. Ribeiro; Letícia C. Mendonça; Roberta H. Piccoli (Veterinary Research Communications, 2016)

Phytochemical profiling as a solution to palliate disinfectant limitations - J. Malheiro; I. Gomes; A. Borges; M. M. S. M. Bastos; J.-Y. Maillard; F. Borges; M. Simões (Biofouling, 2016)

Geographic structuring into vicariant species-pairs in a wide-ranging, high-dispersal plant–insect mutualism: the case of Ficus racemosa and its pollinating wasps - A. Bain; R. M. Borges; M. H. Chevallier; H. Vignes; N. Kobmoo; Y. Q. Peng; A. Cruaud; J. Y. Rasplus; F. Kjellberg; M. Hossaert-Mckey (Evolutionary Ecology, 2016)

Inversion of ambient seismic noise HVSR to evaluate velocity and structural models of the Lower Tagus Basin, Portugal - J. F. Borges; H. G. Silva; R. J. G. Torres; B. Caldeira; M. Bezzeghoud; J. A. Furtado; J. Carvalho (Journal of Seismology, 2016)

Assessment and comparison of the properties of biodiesel synthesized from three different types of wet microalgal biomass - Katkam N. Gangadhar; Hugo Pereira; Hermínio P. Diogo; Rui M. Borges dos Santos; B. L. A. Prabhavathi Devi; R. B. N. Prasad; Luísa Custódio; F. Xavier Malcata; João Varela; Luísa Barreira (Journal of Applied Phycology, 2016)

An antioxidant mechanism of morphine and related derivatives - Rosivaldo S. Borges; Joyce K. L. Vale; Glaécia A. N. Pereira; Andrex A. S. Veiga; João Batista Junior; Albérico B. F. da Silva (Medicinal Chemistry Research, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Oral and endotracheal tubes colonization by periodontal bacteria: a case–control ICU study - A. N. Porto; S. C. Cortelli; A. H. Borges; F. Z. Matos; D. R. Aquino; T. B. Miranda; F. Oliveira Costa; A. F. Aranha; J. R. Cortelli (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Structure and toxicity of clozapine and olanzapine on agranulocytosis - Rosivaldo S. Borges; Gláucio R. Nagurniak; Luana M. D. Queiroz; Cristiane S. F. Maia; Carlos A. L. Barros; Ednilsom Orestes; Albérico B. F. da Silva (Medicinal Chemistry Research, 2016)

A Bayesian framework for the validation of models for subsurface flows: synthetic experiments - M. Akbarabadi; M. Borges; A. Jan; F. Pereira; M. Piri (Computational Geosciences, 2015)

Emergence of azole-resistant Candida albicans in small ruminants - R. S. N. Brilhante; S. T. C. Silva; D. S. C. M. Castelo-Branco; C. E. C. Teixeira; L. C. Borges; P. V. Bittencourt; J. S. de Oliveira; A. J. Monteiro; T. J. P. G. Bandeira; R. A. Cordeiro; J. L. B. Moreira; J. J. C. Sidrim; et al. (Mycopathologia, 2015)

Ground-Motion Simulation in the Lower Tagus Valley Basin - J. F. Borges; M. Bezzeghoud; B. Caldeira; João Carvalho (Pure and Applied Geophysics, 2015)

A computational study for the antioxidant capacity increases in hydroxy-derivatives of paracetamol and salicylic acid - Rosivaldo S. Borges; Tainá G. Barros; Andrex A. S. Veiga; Agnaldo S. Carneiro; Carlos A. L. Barros; Albérico B. F. da Silva (Medicinal Chemistry Research, 2015)

Geostatistics and Geographic Information Systems to Study the Spatial Distribution of Grapholita molesta (Busck) (Lepidoptera: Tortricidae) in Peach Fields - F Duarte; M V Calvo; A Borges; I B Scatoni (Neotropical Entomology, 2015)

Effects of palatable cafeteria diet on cognitive and noncognitive behaviors and brain neurotrophins’ levels in mice - Daniela D. Leffa; Samira S. Valvassori; Roger B. Varela; Jésica Lopes-Borges; Francine Daumann; Luiza M. Longaretti; Ana Luiza F. Dajori; João Quevedo; Vanessa M. Andrade (Metabolic Brain Disease, 2015)

Experimental infection of inbred BALB/c and A/J mice with Massachusetts and Brazilian strains of infectious bronchitis virus (IBV) - Matheus C. Martini; Jacy Gameiro; Tereza Cristina Cardoso; Leonardo C. Caserta; Ana Carolina M. Gualberto; Lara Borges Keid; Trícia M. F. de S. Oliveira; Marcia M. A. B. dos Santos; Clarice W. Arns; Helena L. Ferreira (Archives of Virology, 2015)

Evaluation of the Impact of Different Soil Salinization Processes on Organic and Mineral Soils - J. Jesus; F. Castro; A. Niemelä; Maria-Teresa Borges; A. S. Danko (Water, Air, & Soil Pollution, 2015)

Electrochemical sensor for simultaneous determination of herbicide MCPA and its metabolite 4-chloro-2-methylphenol. Application to photodegradation environmental monitoring - V. Rahemi; J. M. P. J. Garrido; F. Borges; C. M. A. Brett; E. M. P. J. Garrido (Environmental Science and Pollution Research, 2015)

Molecular studies on larvae of Pseudoterranova parasite of Trichiurus lepturus Linnaeus, 1758 and Pomatomus saltatrix (Linnaeus, 1766) off Brazilian waters - Juliana N. Borges; Luiz F. G. Cunha; Daniele F. Miranda; Cassiano Monteiro-Neto; Cláudia P. Santos (Acta Parasitologica, 2015)
Pseudoterranova larvae parasitizing cutlassfish Trichiurus lepturus and bluefish Pomatomus saltatrix from Southwest Atlantic coast of Brazil were studied in this work by morphological, ultrastructural and molecular approaches. The genetic analysis were performed for the ITS2 intergenic region specific for Pseudoterranova decipiens, the partial 28S (LSU) of ribosomal DNA and the mtDNA cox-1 region. We obtained results for the 28S region and mtDNA cox-1 that was amplified using the polymerase chain reaction and sequenced to evaluate the phylogenetic relationships between sequences of this study and sequences from the GenBank. The morphological profile indicated that all the nine specimens collected from both fish were L3 larvae of Pseudoterranova sp. The genetic profile confirmed the generic level but due to the absence of similar sequences for adult parasites on GenBank for the regions amplifyied, it was not possible to identify them to the species level. The sequences obtained presented 89% of similarity with Pseudoterranova decipiens (28S sequences) and Contracaecum osculatum B (mtDNA cox-1). The low similarity allied to the fact that the amplification with the specific primer for P. decipiens didn´t occur, lead us to conclude that our sequences don’t belong to P. decipiens complex.

Novel isomannide-based peptide mimetics containing a tartaric acid backbone as serine protease inhibitors - Bárbara Abrahim-Vieira; Emmerson C. B. da Costa; Pedro H. R. de A. Azevedo; Aline C. Portela; Luiza R. S. Dias; Sergio Pinheiro; Amilcar Tanuri; Anne M. Capaccia; Gustavo T. Ventura; Ronaldo Mohana-Borges; Carlos R. Rodrigues; Alessandra M. T. de Souza; et al. (Medicinal Chemistry Research, 2014)

Isolation and characterization of fifteen polymorphic microsatellite loci for the citrus mealybug, Planococcus citri (Hemiptera: Pseudococcidae), and cross-amplification in two other mealybug species - RENATA F. MARTINS; VERA ZINA; ELSA BORGES DA SILVA; MARIA TERESA REBELO; ELISABETE FIGUEIREDO; ZVI MENDEL; OCTÁVIO S. PAULO; JOSÉ CARLOS FRANCO; SOFIA G. SEABRA (Journal of Genetics, 2014)

To what extent are the fish compositions of a regulated river related to physico-chemical variables and habitat structure? - Taylan M. Mattos; Marcus R. Costa; B. C. T. Pinto; Joyce L. C. Borges; F. Gerson Araújo (Environmental Biology of Fishes, 2014)

Seismicity along the Azores-Gibraltar region and global plate kinematics - M. Bezzeghoud; C. Adam; E. Buforn; J. F. Borges; B. Caldeira (Journal of Seismology, 2014)

Genomic analysis of pandemic and post-pandemic influenza A pH1N1 viruses isolated in Rio Grande do Sul, Brazil - F. H. Sant’Anna; L. G. A. Borges; P. R. V. Fallavena; T. S. Gregianini; F. Matias; R. A. Halpin; D. Wentworth; P. A. d’Azevedo; A. B. G. Veiga (Archives of Virology, 2014)

Nitrogen and carbon availability of liquid and solid fractions of pig slurry obtained using different separation technologies - D. Fangueiro; J. Coutinho; L. Borges; F. Cabral; E. Vasconcelos (Biology and Fertility of Soils, 2014)

Ground motion simulations of the SW Iberia margin: rupture directivity and earth structure effects - M. Bezzeghoud; J. F. Borges; B. Caldeira (Natural Hazards, 2013)

The tautomerism influence on the antioxidant prediction of oxederavone - Sheise A. S. Brígida; Ednilson Orestes; Tainá G. Barros; Carlos A. L. Barros; Agnaldo S. Carneiro; Albérico B. F. da Silva; Rosivaldo S. Borges (Medicinal Chemistry Research, 2013)

Steroidal aromatase inhibitors inhibit growth of hormone-dependent breast cancer cells by inducing cell cycle arrest and apoptosis - Cristina Amaral; Carla Varela; Margarida Borges; Elisiário Tavares da Silva; Fernanda M. F. Roleira; Georgina Correia-da-Silva; Natércia Teixeira (Apoptosis, 2013)

Effect of l-Tyrosine In Vitro and In Vivo on Energy Metabolism Parameters in Brain and Liver of Young Rats - Gabriela K. Ferreira; Giselli Scaini; Milena Carvalho-Silva; Lara M. Gomes; Lislaine S. Borges; Júlia S. Vieira; Larissa S. Constantino; Gustavo C. Ferreira; Patrícia F. Schuck; Emilio L. Streck (Neurotoxicity Research, 2013)

Influence of human immune cells on cancer: studies at the University of Colorado - Tullia C. Bruno; Jena D. French; Kimberly R. Jordan; Oscar Ramirez; Trisha R. Sippel; Virginia F. Borges; Bryan R. Haugen; Martin D. McCarter; Allen Waziri; Jill E. Slansky (Immunologic Research, 2013)

Removal of Metaldehyde Through Photocatalytic Reactions Using Nano-Sized Zinc Oxide Composites - F. C. Doria; A. C. Borges; J. K. Kim; A. Nathan; J. C. Joo; L. C. Campos (Water, Air, & Soil Pollution, 2013)

Gene copy number and differential gene expression in haploid and diploid males of the stingless bee, Melipona quadrifasciata - A. A. Borges; F. C. Humann; M. G. Tavares; L. A. O. Campos; K. Hartfelder (Insectes Sociaux, 2012)

Characterization of cuticular hydrocarbons of diploid and haploid males, workers and queens of the stingless bee Melipona quadrifasciata - A. A. Borges; M. J. Ferreira-Caliman; F. S. Nascimento; L. A. O. Campos; M. G. Tavares (Insectes Sociaux, 2012)

A simple protocol for cryopreservation of zygotic embryos of ten accessions of coconut (Cocos nucifera L.) - O. N’Nan; M. Borges; J.-L. Konan Konan; V. Hocher; J.-L. Verdeil; J. Tregear; A. S. P. N’guetta; F. Engelmann; B. Malaurie (In Vitro Cellular & Developmental Biology - Plant, 2012)

Isotopic fractionation between seawater and the shell of Scrobicularia plana (Bivalvia) and its application for age validation - Sílvia Santos; Joana F. M. F. Cardoso; Valeska Borges; Rob Witbaard; Pieternella C. Luttikhuizen; Henk W. van der Veer (Marine Biology, 2012)

An enterprise architecture approach to forest management support systems design: an application to pulpwood supply management in Portugal - A. F. Marques; J. G. Borges; P. Sousa; A. M. Pinho (European Journal of Forest Research, 2011)

Characterization of wildfires in Portugal - S. Marques; J. G. Borges; J. Garcia-Gonzalo; F. Moreira; J. M. B. Carreiras; M. M. Oliveira; A. Cantarinha; B. Botequim; J. M. C. Pereira (European Journal of Forest Research, 2011)

The Azores archipelago, Portugal: improved understanding of small island coastal hazards and mitigation measures - H. Calado; P. Borges; M. Phillips; K. Ng; F. Alves (Natural Hazards, 2011)

Management of chestnut plantations for a multifunctional land use under Mediterranean conditions: effects on productivity and sustainability - A. Martins; G. Marques; O. Borges; E. Portela; J. Lousada; F. Raimundo; M. Madeira (Agroforestry Systems, 2011)

The Azorean Biodiversity Portal: An internet database for regional biodiversity outreach - PAULO A.V. BORGES †; ROSALINA GABRIEL †; ANA M. ARROZ †; ANA COSTA †; REGINA T. CUNHA †; LUÍS SILVA †; ENÉSIMA MENDONÇA †; ANTÓNIO M. F. MARTINS †; FRANCISCO REIS †; PEDRO CARDOSO † (Systematics and Biodiversity, 2010)

Erratum to: Effects of fish farming on plankton structure in a Brazilian tropical reservoir - Paula A. F. Borges; Sueli Train; Juliana D. Dias; Cláudia C. Bonecker (Hydrobiologia, 2010)

Higher dopamine transporter density in Parkinson’s disease patients with depression - Andre C. Felicio; Tais S. Moriyama; Clecio Godeiro-Junior; Ming C. Shih; Marcelo Q. Hoexter; Vanderci Borges; Sonia M. A. Silva; Edson Amaro-Junior; Luiz A. F. Andrade; Henrique B. Ferraz; Rodrigo A. Bressan (Psychopharmacology, 2010)

DIRDOP: a directivity approach to determining the seismic rupture velocity vector - Bento Caldeira; Mourad Bezzeghoud; José F. Borges (Journal of Seismology, 2010)

Effects of fish farming on plankton structure in a Brazilian tropical reservoir - Paula A. F. Borges; Sueli Train; Juliana D. Dias; Cláudia C. Bonecker (Hydrobiologia, 2010)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

An approach to cork oak forest management planning: a case study in southwestern Portugal - A. Costa; A. C. Oliveira; F. Vidas; J. G. Borges (European Journal of Forest Research, 2010)

Effects of soil management practices and irrigation on plant water relations and productivity of chestnut stands under Mediterranean conditions - A. Martins; F. Raimundo; O. Borges; I. Linhares; V. Sousa; J. P. Coutinho; J. Gomes-Laranjo; M. Madeira (Plant and Soil, 2010)

Vehicular particulate matter emissions in road tunnels in Sao Paulo, Brazil - Odón R. Sánchez-Ccoyllo; Rita Y. Ynoue; Leila D. Martins; Rosana Astolfo; Regina M. Miranda; Edmilson D. Freitas; Alessandro S. Borges; Adalgiza Fornaro; Helber Freitas; Andréa Moreira; Maria F. Andrade (Environmental Monitoring and Assessment, 2009)

Response of the Egg Parasitoids Trissolcus basalis and Telenomus podisi to Compounds from Defensive Secretions of Stink Bugs - Raúl A. Laumann; Michely F. S. Aquino; Maria C. B. Moraes; Martín Pareja; Miguel Borges (Journal of Chemical Ecology, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Ranking protected areas in the Azores using standardised sampling of soil epigean arthropods - P.A.V. Borges; C. Aguiar; J. Amaral; I.R. Amorim; G. André; A. Arraiol; A. Baz; F. Dinis; H. Enghoff; C. Gaspar; F. Ilharco; V. Mahnert; et al. (Biodiversity and Conservation, 2005)

Simultaneous observation of collagen and elastin in normal and pathological tissues: analysis of Sirius-red-stained sections by fluorescence microscopy - L. F. Borges; S. R. Taboga; P. S. Gutierrez (Cell and Tissue Research, 2005)

Segmentation of the fibro-glandular disc in mammogrms using Gaussian mixture modelling - R. J. Ferrari; R. M. Rangayyan; R. A. Borges; A. F. Frère (Medical & Biological Engineering & Computing, 2004)

Identification of the breast boundary in mammograms using active contour models - R. J. Ferrari; A. F. Frère; R. M. Rangayyan; J. E. L. Desautels; R. A. Borges (Medical & Biological Engineering & Computing, 2004)

Hematologic and serum biochemical values for jundiá (Rhamdia quelen) - Adriana Borges; Luciana V. Scotti; Daniele R. Siqueira; Daiane F. Jurinitz; Guillermo F. Wassermann (Fish Physiology and Biochemistry, 2004)

Hepatotoxicity of 3,4-methylenedioxyamphetamine and ?-methyldopamine in isolated rat hepatocytes: formation of glutathione conjugates - Maria Lourdes Bastos; Mrcia Carvalho; Nuno Milhazes; Fernando Remio; Fernanda Borges; Eduarda Fernandes; Francisco Amado; Terrence J. Monks; Flix Carvalho (Archives of Toxicology, 2004)

Changes in the distribution of sardine eggs and larvae off Portugal, 1985–2000 - Y. Stratoudakis; M. Bernal; D. L. Borchers; M. F. Borges (Fisheries Oceanography, 2003)
Generalized additive models (GAMs) were fitted to sardine ( Sardina pilchardus ) egg distribution data from three daily egg production method surveys. The results showed that the area of egg cover off Portugal decreased significantly from 11 800 km 2 in 1988 to 7000 km 2 in 1997 and 7400 km 2 in 1999. This is because of a significant reduction in sardine egg presence off northern Portugal, GAM estimated areas being similar or higher in the late 1990s for southwestern and southern Portugal. The distributional area covered by larvae was not estimated for 1988 (larval distribution extended beyond the survey area), although it was probably higher than the 9600 km 2 for 1997 and 5500 km 2 for 1999. In 1997 and 1999, the Gulf of Cadiz was also sampled, indicating extensive areas with sardine eggs and larvae (more than 50% of the total area of distribution off Portugal). Standardized data from 15 ichthyoplankton surveys between 1985 and 2000 show a decline in the mean probability of egg presence within the Portuguese continental shelf from the mid‐1980s to the late‐1990s, because of a marked reduction in egg presence off northern Portugal. Sardine larval data from the same surveys suggest that the reduction in mean probability of presence in the north is less marked than for eggs (although this comparison ignores the presence of sardine larvae beyond the continental shelf in the 1980s). Similar changes off northern Portugal and western Galicia are observed in commercial sardine catches and the acoustically estimated area of fish distribution. It is possible that the observed decline in spawning area off northwestern Iberia during the 1990s is indirectly reflecting the prevalence of environmental conditions detrimental to sardine recruitment (northerly winds during winter that favour coastal upwelling and offshore transport), which have reduced the spawning contribution of young fish in that area.

Role of metabolites in MDMA (ecstasy)-induced nephrotoxicity: an in vitro study using rat and human renal proximal tubular cells - Má rcia Carvalho; Gabrielle Hawksworth; Nuno Milhazes; Fernanda Borges; Terrence Monks; Eduarda Fernandes; Fé lix Carvalho; Maria Bastos (Archives of Toxicology, 2002)

Phagocytosis and giant cell formation at 0° C by macrophage (MØ) of Notothenia coriiceps - J. R. M. C. Silva; N. A. Staines; F. J. Hernandez‐Blazquez; L. R. Porto‐Neto; J. C. S. Borges (Journal of Fish Biology, 2002)
Macrophages adhered to round glass coverslips that had been implanted into the abdominal cavity of Notothenia coriiceps , collected from Admiralty Bay, King George Island, and removed and incubated in vitro for 4 h at 0° C at various intervals. The macrophages phagocytosed yeast Saccharomyces cerevisiae cells suspended in saline. Bi‐nuclear macrophages were first observed after 6 h. The formation of giant cells and their phagocytic activity was observed only in fish which had been injected with 1 ml of Bacillus of Calmette and Guerin (BCG)‐suspension 24 h before coverslip implantation and the coverslips removed 15 days after the implantation. Phagocytosis and the formation of giant cells in an Antarctic fish at 0° C is described for the first time.

Morphological and functional characterization of beige mouse adrenomedullary secretory vesicles - Ricardo Borges; Ruth Jaén; Francisco Freire; José F. Gómez; Cristina Villafruela; Eulalia Yanes (Cell and Tissue Research, 2001)

Effect of phenylalanine and p-chlorophenylalanine on Na+, K+-ATPase activity in the synaptic plasma membrane from the cerebral cortex of rats - Emílio L. Streck; Patrícia T. Edom; Maria E. Noriler; Luiz F. Borges; Zilda L. Pontes; Edino Parolo; Carlos S. Dutra-Filho; Clóvis M. D. Wannmacher; Angela T. S. Wyse (Metabolic Brain Disease, 2000)

Thermococcus waiotapuensis sp. nov., an extremely thermophilic archaeon isolated from a freshwater hot spring - Juan M. González; D. Sheckells; Mareike Viebahn; Donara Krupatkina; Kimberly M. Borges; F. T. Robb (Archives of Microbiology, 1999)

Calcium channel subtypes and exocytosis in chromaffin cells: a different view from the intact rat adrenal - F. Santana; P. Michelena; R. Jaén; A.G. García; R. Borges (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Alanine Prevents the Decrease of Na+,K+-ATPase Activity in Experimental Phenylketonuria - Angela T.S. Wyse; Maria E. Noriler; Luiz F. Borges; Petterson J. Floriano; Cleide G. Silva; Moacir Wajner; Clovis M.D. Wannmacher (Metabolic Brain Disease, 1999)

Source Parameters of Old Earthquakes: Semi-Automatic Digitization of Analog Records and Seismic Moment Assessment - P. Teves-Costa; J. F. Borges; I. Rio; R. Ribeiro; C. Marreiros (Natural Hazards, 1999)

ber Wuchsstoff-Mangelerscheinungen an Hefe-Riesenkolonien - F. Weinfurtner; F. Eschenbecher; W. Borges (Archives of Microbiology, 1960)